Inspection of Hygiene and Vaccination of Broiler Chickens in Maimana City and Pashtonkot District - Noorzad, Mohammad Arif; Saadat, Saifullah (Journal for Research in Applied Sciences and Biotechnology, 2024)
Poultry farming is a good means of generating income and employment for the people of a country. In addition to having a good income, this industry; it prepares good food for humans, which is economical on the one hand, and on the other hand, chicken products are the best food for humans in Afghanistan and in the world. The purpose of this research is to clarify and explain the current state of hygiene and vaccination of broiler chickens. The research that has been done is a field research and three methods of observation, interview and questionnaire have been used to collect information. The result of the research showed that in 55 percent of Maimane farms, hygiene issues were observed, in 20 percent of farms, the hygiene conditions were relatively good, and in the broiler industry, in the research areas, respectively, ND+IB, IBD- A, IBD-B, and ND were the mentioned vaccines used in both research areas. The only difference between them in Maimana and Pashtankot district was the percentage of their implementation or use, so that ND and IB in Maimana in the period First, 100% was used, while 80% was used in the farms of Pashtankot district, and the amount of other vaccines were also different in Maimanah and Pashtankot districts.